Bioremediation potential of tree-level plant vegetation UIN Raden Mas Said Surakarta campus as an alternative solution to environmental problems towards a green campus. - Prasetyo, Angga Dwi (Universitas Islam Negeri Mataram, 2023)
Environmental problems become actual and interesting issues to discuss. Environmental problems are not only in water, soil and living things but also include air pollution. One of the environmental solutions can use bioremediation, Educational Institutions can also participate in environmental solutions by becoming a green campus. The purpose of this study is to see the potential of bioremediation of tree-level plant vegetation UIN Raden Mas Said Surakarta as an alternative solution to environmental problems towards a green campus. This research was conducted from July-October 2023, plant classification was carried out thoroughly in the campus area, then a meta-analysis was carried out for its potential as bioremediation and green campus potential. Based on the results of research at the UIN Raden Mas Said Surakarta campus, there are 58 types of plants with a total of 670 plants with the most types of plants red shoots (Syzygium paniculatum Gaertn.) 12% and Ketapang kencana (Terminalia mantaly) 11%. Furthermore, the results of the meta-analysis found that the potential for vegetation bioremediation at UIN Raden Mas Said Surakarta as phytoremediation where plants act as bioremediation agents, while the potential of UIN Raden Mas Said Surakarta as a green campus based on the UI GreenMetric Guidelines 2022 Standards has met several criteria and indicators of green campus achievements, but to become a green campus requires the participation of various parties, both leaders and the academic community and students so that UIN Raden Mas Said Surakarta can get the title of green campus.